Digital Mathematics Module Based on Problem-Based Learning Model with Classpoint Mathematics Gamification - Arnellis, Arnellis; Zulnaidi, Hutkemri; Yuanita, Putri; Yerizon, Yerizon; Sari, Atika; Syaputra, Hamdani (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Problem solving skills is one of the most important skills students should achieve in mathematics. However, students' mathematical problem-solving skills still low. This research offers classpoint mathematics gamification in digital mathematics module based on problem-based learning. Thus, this research was conducted to develop a valid, practice, and effective mathematics digital module based on problem-based learning model with classpoint mathematics gamification (ChePomathGo) in improving students’ problem solving skills. This study used the Plomp development model, including the preliminary research, prototyping, and assessment phases. Preliminary research involving 32 students and 1 teacher and prototyping and assessment phase involving 9 students in seventh grade junior high school. Data analysis used are descriptive analysis. The result shows that the mathematics digital module based on problem-based learning model with ChePomathGo is valid with an average score of 3.67 (very valid category), practice based on students’ and teachers’ positive responses, and effective to improve students’ problem solving skills based on the results of the students' mathematical problem-solving skills test in small group evaluations with an average score of 75% (effective category). The implications of this research is the digital mathematical module developed can be a guidelines for researchers and teachers to improve students’ mathematical problem-solving skills.